(untitled) (Medico Legal Update, 2020)
Pleomorphic adenoma (PA) is a benign tumor of the salivary glands that has components of both epithelial and mesenchymal origin. The most common site for the PA is the parotid or submandibular glands. On rare occasions, the tumor may arise from the minor salivary glands and present as an intraoral swelling over the hard palate or lip. But the anterior hard palate is not the commonest site for PA. We report the case of a 42-year old man who came with a complaint of a swelling in the anterior region of the hard palate and later diagnosed as pleomorphic adenoma based on histopathological examination.